Risk Factors of Relapse After Smoking Cessation: Results in China Family Panel Studies From 2010 to 2018 - Hu, Naifan; Yu, Zhenfan; Du, Yurun; Li, Jiangping (Frontiers in Public Health, 2022)
Tobacco use is still highly prevalent in the world in spite of the tobacco control efforts made by the governments. In view of the harm of smoking and relapse after smoking cessation, the purpose of this study is to establish a competitive risk model to determine potential risk factors of smoking relapse. The population-based cohort of ex-smokers over the age of 18 was obtained from the China Family Panel Studies (CFPS) database from 2010 to 2018. Competing risk models were conducted to identify the risk factors for relapse. A total of 1,019 subjects were included in this study, of which 311 (30.52%) relapsed during the follow-up period. A multivariate analysis indicated that age<40 (HR19.142 95% CI: 10.641 34.434, P <0.01), cohabitation (HR: 9.982; 95% CI: 4.077 24.441, P<0.01) and often depression (HR 1.422; 95% CI, (1.081 1.87), P= 0.01) were associated with a great risk of relapse while age of quitting smoking<60 (HR: 0. 436; 95% CI: 0.229 0.831, P <0.01) and joining Chinese Communist Party (HR 0.611; 95% CI, 0.397 0.939, P= 0.03) were reverse risk factors for relapse. Approximately 3 in 10 ex-smokers was observed to relapse, in the face of such a serious situation, it is urgent to take action to control smoking. Therefore, tobacco control action can be set about from prevention and cutting off the risk factors of relapse. Taking targeted measures from the risk factors of relapse to reduce tobacco use and exposure is also the direction of the efforts of Chinese government.